Evolusi Data, Information, Knowledge, Wisdom (DIKW) Pada Pengelolaan Data Pelanggan Baru Berbasis CRM - Pranakusuma Sudhana (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
This study aims to provide information obtained from new customer data, which can then develop into knowledge and even wisdom in order to improve sales performance at an Educational Institution XYZ. This research used descriptive analysis method with frequency analysis technique and comparative method. The research results show the following information: (1) the conversion rate of prospects to become students is only 0.44%; (2) 94% of new students are girls; (3) 89% of new students are between 18 – 21 years old which is the normal age for high school graduates; (4) 78% of new students come from outside the region; and (5) 61% of new students have lead scores between 50 – 100. From this information, knowledge is obtained that the student profiles of these institutions are women aged 18 – 21 years and come from outside the region, who have participated in several marketing events by institutions. It is hoped that this knowledge can be utilized by institutional management to make wise decisions (wisdom).